The Development of UTHM Bus Tracking Mobile Application Using an Object-Oriented Approach - Muhammad Izryzza Nazrin Jafni; Nur Ariffin Mohd Zin (Applied Information Technology And Computer Science, 2023)
This study focuses on the development of the UTHM Bus Tracking Mobile Application, a mobile-based system aimed at addressing the problem faced by Universiti Tun Hussein Onn Malaysia (UTHM) students in tracking the location of the bus. The objective of this research is to provide an effective solution to enhance the bus transportation experience for UTHM students. The system was developed using an object-oriented approach, employing the Waterfall model to ensure a systematic development process. The Flutter framework and Firebase server were utilized for application development and data storage, respectively. Key findings indicate that the UTHM Bus Tracking Mobile Application enables students to track the bus location, thereby improving the efficiency of public transportation. The discussion highlights the significance of this system in students’ daily lives and suggests possibilities for future enhancements.